Cardiometabolic Risk in Acromegaly: A Review With a Focus on Pasireotide - Puglisi, Soraya; Ferraù, Francesco; Ragonese, Marta; Spagnolo, Federica; Cannavò, Salvatore (Frontiers in Endocrinology, 2020)
Acromegaly is a disease due to chronic GH excess and to the consequent raise in IGF-1 levels. This rare endocrine condition is associated with metabolic alterations, such as hyperglycaemia, dyslipidaemia, and systemic arterial hypertension, which in addition to GH-excess related cardiovascular changes play a critical role in increasing cardiovascular risk and mortality rate. Biochemical control of acromegaly, achieved by means of surgical and/or medical treatment, positively impacts on cardiovascular risk factors and metabolic alterations, reducing overall patients’ mortality. However, treatment modalities of acromegaly and disease control differently impact on glucose homeostasis and lipid changes, and consequently on cardiometabolic risk. In this regard, pasireotide was shown to significantly influence glucose metabolism. This review summarizes cardiometabolic consequences of acromegaly and of its treatment, focusing on available data on the effects of medical therapy with pasireotide on factors influencing the cardiometabolic risk.